MATHEMATICAL MODEL OF A ARTICULATED FRAME WITH A CAB TURN MECHANISM - Nikita V. Froltsov; Mikhail A. Bykov; Alexey I. Ponomarev; Maksim V. Sidorov (International Journal of Advanced Studies, 2023)
Tractors are technological energy means used for general mechanization and automation of agricultural production, as well as for the transportation of finished raw materials. Tractors of traction class 8 must have high productivity and efficiency, in order to achieve the best results, in the shortest agrotechnical time.